Insights on the process to develop Australia’s first national climate risk assessment - Fanny A. Boulaire; Stephen Cook; Aysha Fleming; Lygia Romanach; Tim Capon; Murni Po; Rebecca Darbyshire; Guy Barnett; Sonia Bluhm; Brenda B. Lin (iScience)
Summary: Countries are undertaking national climate risk assessments to help decision-makers respond effectively to climate change impacts. Australia has also started this process, with the release in early 2024 of the first pass assessment report of its National Climate Risk Assessment.This paper describes our experiences of the process undertaken in Australia to conduct a first pass qualitative assessment of climate risks and compare it with the learnings gathered from a desktop review of 15 other national climate risk assessments. Highlighting similarities and differences in approaches, this paper offers insights for others embarking on a similar journey or improving existing ongoing processes. It identifies four process themes that could contribute to a common framework for these assessments, while acknowledging the need for tailored approaches. Having a common framework could increase awareness and incentives for international collaboration on common or shared risks, and lead to more coordinated climate mitigation and adaptation actions.